Diazachlorin and diazabacteriochlorin for one- and two-photon photodynamic therapy. Issue 98 (21st November 2018) - Longevial, Jean-François; Yamaji, Ayaka; Aggad, Dina; Kim, Gakhyun; Chia, Wen Xi; Nishimura, Tsubasa; Miyake, Yoshihiro; Clément, Sébastien; Oh, Juwon; Daurat, Morgane; Nguyen, Christophe; Kim, Dongho; et al.
Abstract : Diazachlorin and diazabacteriochlorin were prepared and their activity for photodynamic therapy was investigated. Abstract : Diazachlorin and diazabacteriochlorin have been prepared through reduction of diazaporphyrin and their in vitro and in vivo activity in photodynamic therapy has been investigated.